Evaluation of the best e-commerce websites in Malaysia using Fuzzy AHP / Siti Nor Nadrah Muhamad, Umairah Najwa Zaib and Mohd Halimi Ab Hamid - Muhamad, Siti Nor Nadrah; Zaib, Umairah Najwa; Ab Hamid, Mohd Halimi (UiTM Cawangan Perlis, 2022)
E-commerce, often known as electronic commerce, is a method of doing business that involves purchasing and selling products and services via a digital network like the internet. Since there are various types of e-commerce websites in Malaysia like Lazada, Shopee and PGMall, the consumers have difficulties choosing which e-commerce websites to access for online shopping. The organisation also finds it hard to make a judgement about which sites to use for their online transaction and human judgement for decision making is not reliable in our daily life. The Fuzzy AHP method was used in this study to select the best e-commerce websites in Malaysia. The research aim is to determine the criteria when choosing e-commerce websites, identify sub-criteria that impact e-commerce website rankings and investigate the best rank of e-commerce in Malaysia. In this study, two decision-makers examine three criteria and eight sub-criteria to determine the best e-commerce websites in Malaysia. There are three websites to choose from Shopee, Lazada, and PGMall. The criteria are system quality, information quality, and service quality. Besides, the sub-criteria are access speed, visual appearance, response time, reliable information, update information, accurate information, tracking order status, and payment alternatives. The primary data was used by distributing a set of questionnaires to the experts in the field. Shopee is the best e-commerce website in Malaysia, according to the results, with a normalised score of 0.4488. Lazada comes in second with a normalised 0.4360, and PGMall with a normalised 0.1153. As a result, Shopee outperforms the other two online transaction platforms, Lazada and PGMall.